The socio economic implications of ethno-religious conflict in Nigeria (2022)
Ethno-religious conflict and its attendant implications have become the Order of the day in Nigeria and its economic effects on the nation over the years are mindboggling. Many houses and means of livelihood destroyed resulting in poverty among many families. Existing studies on ethno-religious conflict have focused mainly on the political, spiritual and ethnic dimensions to the neglect of how it has impacted negatively on the economic development of the nation, thereby making the country to take a backseat among the comity of nations. Ironically, as religion could be used as instrument of social harmony in many civilizations, it could also serve as a motivation for conflict, hence its description as a double edged sword. Our findings revealed that bad governance, marginalization/inequality, weak security network and corruption are the major factors that precipitated ethno-religious conflict in Nigeria. It is on this note that this paper discussed the socio-economic implications of ethno-religious conflict on Nigeria. In particular, the paper investigated the genesis of ethno-religious conflict in Nigeria, its causes and effects and how the incessant ethno-religious conflict can be addressed headlong thereby bringing about a peaceful co-existence among the people which will invariably result in monumental development in the nation.